Addiction to Electronic Devices and Its Negative Impact on the Decline of Academic Achievement among University Students: The Concern of Faculty Members at the University of Al-Zawiya. (Al-Farooq Journal of Sciences, 2026)
This study aimed to explore the impact of addiction to electronic devices on the academic achievement of university students, identify the causes of this addiction, and examine its psychological, social, and educational effects, in addition to exploring appropriate solutions to reduce it. The results showed that university students spend long hours using the Internet, electronic games, and applications, which leads to decreased concentration and academic performance, as well as psychological and health problems such as anxiety, stress, back pain, and sleep disturbances, in addition to weakened social interaction. The study also indicated that the level of addiction ranges from moderate to high, with a clear negative effect on academic performance. Based on these findings, the study recommended setting specific times for using the Internet and applications, encouraging students to engage in physical and social activities away from screens, seeking psychological support when needed, and activating the role of families, educational institutions, and media in raising awareness about the risks of addiction and promoting digital and health literacy among students.
Keywords: Addiction, Electronic Devices, Academic Achievement, University Students, Faculty Members